Steal back the Mona Lisa! - McCarthy, Meghan (Orlando : Harcourt, 2006)
When crooked crooks steal the Mona Lisa from the Louvre, Special Agent Jack is sent on a dangerous mission to steal it back. Includes facts about the painting.
Ages 4-8.
Accelerated Reader/Renaissance Learning
Keywords: Leonardo, -- da Vinci, -- 1452-1519. -- Juvenile fiction; Leonardo, -- da Vinci, -- 1452-1519. -- Fiction; Crime -- Fiction; Spies -- Fiction; Humorous stories